Approaches of Abu Rayhan Al-Biruni in the study of Hinduism: an analytical discourse - Gilani, Sayyid Muhammad Yunus (2015)
The Study of religions is a legacy of the Muslim scholars: Ibn Hazm, Al-Jahiz, Al-Biruni, Shahrastani, Kiranvi, Ibn Taymiyyah, Faruqi and many others who were internationally renowned scholars significantly contributed in this field. Among them Abu Rayhan al-Biruni is an unparalleled intellectual in the discipline of religious studies. This study attempts to highlight al-Biruni’s approaches as well as his views on the field of Hindu culture and civilization to provide a Muslim intellectual understanding of Hinduism. It follows the qualitative method and analyses the data which is mainly based on available relevant books or manuscripts in various libraries. The study however will show the new perspectives of al-Biruni’s scholarship to other religions especially the Hindu religion in order to improve religious harmony in society and overcome the adversities among contemporary religious groups. The study will also contribute to demonstrate the methodological approaches that he used to understand Hindu culture and civilization.